Resveratrol Targets AKT1 to Inhibit Inflammasome Activation in Cardiomyocytes Under Acute Sympathetic Stress - Wang, Rui; Wang, Yanming; Wu, Jimin; Guo, Yanli; Xiao, Han; Zhang, Youyi; Ma, Ketao (Frontiers in Pharmacology, 2022)
Resveratrol shows promising anti-inflammatory effects in recent clinical trials, however its function in cardiovascular patients remains conflicting, suggesting there may be new mechanisms underlying its cardioprotective activity. Acute sympathetic stress induces early activation of the NLR family, pyrin domain containing 3 (NLRP3) inflammasome in cardiomyocytes as a critical step for triggering cardiac inflammation. Thus, this study explored targets of resveratrol activity involved in the inhibition of early inflammasome activation in cardiomyocytes following acute sympathetic stress. Network pharmacology was used to analyze common candidate targets in the sympathetic stress pathway, resveratrol activity, and myocardial inflammation and showed the Phosphoinositol 3 ⁃ kinase (PI3K)/serine threonine protein kinase (Akt) signaling pathway and the target AKT1 may play a critical role. Molecular docking provided support for potential binding of resveratrol on AKT1. Furthermore, the effect of resveratrol on AKT1 activation was determined in cardiomyocytes. resveratrol dose-dependently inhibited AKT1 activation after activation of β-adrenoceptor. The AKT1 inhibitor A-674563 suppressed the activation of the NLRP3 inflammasome in cardiomyocytes following β-adrenoceptor activation, suggesting that AKT1 is a critical regulator molecule upstream of the NLRP3 inflammasome. Consistently, treatment with resveratrol suppressed β-adrenoceptor-mediated NLRP3 inflammasome activation in both cardiomyocytes and mouse hearts, as well as the resultant cardiac inflammation. In conclusion, resveratrol targets AKT1 to inhibit NLRP3 inflammasome activation in cardiomyocytes and cardiac inflammation following acute sympathetic stress. AKT1 is an important target of resveratrol, which should be considered as a treatment option for cardiovascular patients, especially those at risk of acute sympathetic stress.